Laser in Dermatological Treatments: A Review of How Laser is used in Treating Skin Issues such as Acne, Scars, and Pigmentation (American Journal of Engineering , Mechanics and Architecture (2993-2637), 2024)
Laser technology has emerged as a pivotal tool in dermatological treatments, offering a range of therapeutic options for various skin conditions, including acne, scars, and pigmentation disorders. This review explores the mechanisms by which different types of lasers, such as ablative, non-ablative, fractional, and Q-switched lasers, are employed to address these common dermatological concerns. The effectiveness of laser treatments in stimulating collagen production, remodeling scar tissue, and reducing melanin concentration is examined, alongside an analysis of the safety profiles and potential side effects associated with each laser type. Additionally, the review highlights the importance of personalized treatment plans tailored to individual patient characteristics, such as skin type and the severity of the condition, to maximize therapeutic outcomes. Emerging trends in laser technology, including the development of more targeted and less invasive approaches, are also discussed. This comprehensive review aims to provide clinicians and researchers with a deeper understanding of the current state of laser-based dermatological treatments, as well as future directions in the field.